VD_FINDINFO 670 vom 21. August 2023 - VD Tribunal cantonal (2023)
FRAIS DE LA PROCÉDURE, FAUTE PROFESSIONNELLE, ILLICÉITÉ | 12 let. a LLCA, 393 al. 1 let. a CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH)